NILAI-NILAI PENDIDIKAN AKHLAK DALAM KITAB WAṢĀYĀ AL-ĀBĀ' LIL ABNĀ KARYA SYEKH MUHAMMAD SYĀKIR DAN IMPLIKASINYA TERHADAP PEMBELAJARAN PAI DI SEKOLAH - Ghita Widya Pratiwi, - (2022)
Morals are one of the problems that occur today, especially in the world of education. Among the most basic problems in the world of education is the lack of strengthening of the values of moral education, especially those contained in previous moral books which are still relevant today. Discussions related to the works of Muslim thinkers who discuss moral education are still lacking in references, especially in the current modern era. So, it is necessary to strengthen moral education by utilizing various innovative ways. This study seeks to examine the values of moral education in the book Waṣāyā Al-Abā Lil Abnā by Sheikh Muhamamd Syākir. This research is very important to study, because it can be useful not only in educational institutions, but also in Islamic boarding schools and the general public. This research was conducted using a qualitative approach with library research methods. The sources are obtained from primary data in the form of the book Waṣāyā Al-Abā Lil Abnā and secondary data in the form of a translation of the book. The results of this study found that there are twenty values of moral education that have been classified into five scopes of morals, namely morals towards Allah, morality towards Rasūlullāh, morals towards oneself, morals towards parents, and morals towards friends and society. The results of this study also have implications for PAI learning in schools, namely the involvement in the book of Waṣāyā Al-Abā Lil Abnā by Sheikh Muhammad Syākir towards the objectives, materials, methods, PAI teachers and students by trying to adopt various values of moral education contained in the book.